THE CHARACTER EDUCATION CURRICULUM IN ISLAMIC BOARDING SCHOOLS: A CASE STUDY OF MAN INSAN CENDEKIA SERPONG - Pahrurroji, Pahrurroji (Edukasi Islami: Jurnal Pendidikan Islam, 2025)
Purpose: This study analyzes the implementation of the character education curriculum at MAN Insan Cendekia Serpong, one of Indonesia’s leading Islamic boarding schools. Method: Using a descriptive qualitative approach, data were collected through observations, interviews, and document analysis. Result: The findings reveal that character education is integrated into both general and religious subjects and reinforced through dormitory programs, daily moral guidance, and student activities. Key values emphasized include honesty, responsibility, discipline, religiosity, and leadership. Conclusion: The systemic and synergistic model that combines formal and non-formal education has proven effective in shaping students’ holistic character. The practical implication is that this integrative-holistic curriculum model can be replicated in other Islamic schools with contextual adjustments to meet local needs.